Theoretical prerequisites for the use of artificial intelligence tools in the implementation of a three-tier model of judicial and law enforcement activities in the Republic of Kazakhstan - Dulatbekov, N.O.; Bachurin, S.N. (Bulletin of the Karaganda University “Law Series”, 2024)
The purpose of this study is to substantiate the need to use artificial intelligence tools in judicial and law enforcement activities, in the context of building a new three-tier model. The ongoing changes in the Republic of Kazakhstan regarding the reform of legislation in general, and criminal, criminal — due process, in particular, against the background of the development of technologies related to artificial intelligence, they are forced to rethink previously established theoretical positions in science about the paramount importance of a person in the implementation of justice.The development of our own high-quality information systems and products in the Republic of Kazakhstan in the banking sector, aggregators of sales of goods and services, and education is becoming a vivid confirmation of the need to create them in such a sensitive area as justice. What is the scope of their implementation, the tasks and goals have not yet been determined, since the previous scientific discussion on this area of research did not lead to any specific results. In a separate direction, the authors outlined the theoretical prerequisites for the use of artificial intelligence tools in the study of issues in the implementation of a three-tier model of judicial and law enforcement activities in the Republic of Kazakhstan. The conducted research allowed us to conclude about the expediency and rationality of using artificial intelligence tools within the framework of national law, including at the early stages of pre-trial criminal proceedings, with the active use of forensic potential and ending with the implementation of justice in the judicial stages.